EVALUATION OF CLINICAL USE HABİTS OF TUMOR MARKER TESTS - Soycan MIZRAK (Rojan GÜMÜŞ, 2020)
Tumor markers(TMs) result from the re-expression of substances by embryologically related tissues. Many are found in different tumors of the same tissue. Therefore, they have low specificity and aren't sufficiently sensitive as a screening test. The aim of this study is to evaluate the TM requesting habits of clinicians in Usak Training and Research Hospital, and the appropriateness of the test requests with the diagnosis. Material-Method: Data of 6998 serum TMs requested from 3316 patients between May 1 and July 31, 2019 were obtained from Laboratory Information System and grouped as sex, age, disease diagnoses and multiple requests (more than 3 tests simultaneously). Compliance with diagnosis was evaluated as appropriate or inappropriate based on published guidelines for indications for TM requests. Results: 796 of the 6998 TMs requested from inpatients (2.75 markers/patient) and 6202 from outpatients (2.04 markers/patient). Most TMs were made in the 50-70 age range (48.3%). Multiple TMs were mostly demanded from the Obstetrics and Gynecology Clinic with the diagnosis of menstrual irregularity. Also, 1078 of 1408 total PSA and 28 of 191 free PSA tests were requested with appropriate pre-diagnosis. Conclusion: This study is an example of the use of data mining for conformity assessment purposes of the TM requests. Accordingly, it was found that the TMs were often incompatible with the diagnosis and were used for general screening purposes. In order to minimize misuse, evidence based indicators should be developed and clinician awareness should be increased by creating test request algorithms that support the diagnosis.